Peer Creativity and Academic Achievement - Max van Lent (Institute of Labor Economics (IZA), 2024)
This paper studies the relationship between the creative abilities of study peers and academic achievement. We conduct a novel large scale field experiment at university, where students are randomized into work groups based on their score on a creativity test prior to university entry. We first show that the creative abilities of peers matter for a student's academic achievement. A one standard deviation higher creativity peer group improves study performance by 8.4 to 10 percentage points. Notably, this effect is driven by the average group creativity, there is no special impact of creative superstars. Further analysis suggests that students exposed to creative peers become more creative, but do not adjust their overall study effort. This is in line with the idea that creative approaches and questions of peers help students to master the study material better. Overall, our study highlights the importance of peer effects of creative students in shaping academic outcomes.
Keywords: I21; I24; J24; 330; peer effects; academic achievement; creativity; field experiment